Marxism and the Crisis of Development in Prewar Japan. - Hoston, Germaine A. (Princeton legacy library., 2014)
This study is a comprehensive analysis of the Marxist debate in Japan over how capitalism developed in that country. Originally published in 1987. The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These paperback editions preserve the original texts of these important books while presenting them in durable paperback editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in t.